Uncovering the role of virtual agents in co-creation contexts: An application to the online wine business. Issue 6 (12th April 2018) - Castellano, Sylvaine; Khelladi, Insaf; Charlemagne, Justine; Susini, Jean-Paul
Abstract : Purpose: The purpose of this paper is to understand the roles of virtual agents in a virtual co-creation context by exploring their influence on online trust. An empirical study is conducted in the French online wine business to analyse the impacts of different dimensions of virtual agents on generating online trust. Design/methodology/approach: Primary data were collected through a questionnaire targeting French online wine shoppers. Findings: The results demonstrate a positive effect of the utility and hedonic functions of virtual agents on online trust. The findings also confirm the moderating role of the perceived risk. Research limitations/implications: The authors' convenience sample shows a bias towards a lack of familiarity with virtual agents. Practical implications: Wine business actors need to consider their customers' profiles in order to better adapt virtual agents' functionality and hence improve their customers' level of online trust while reducing their risk perception. Additionally, understanding virtual agents' roles can help identify the underlying mechanisms that emerge in a co-creation process. Originality/value: The study contributes to a better understanding of the human dimension of co-creation by examining the different roles of virtual agents as sources of customers' online trust.